Identification of Legal Aspects of the Environment and Patterns of Citizens' Awareness of Environmental Safety, Sustainability, and Balance - Budi Sulistiyo Nugroho; Irma Rachmawati Maruf; Adi Mursalin; B.M.A.S. Anaconda Bangkara; Endang Fatmawati (LEGAL BRIEF, 2022)
Efforts to save the environment have been carried out in various ways, including creating policies and implementing the Law on citizen awareness of the importance of safety, balance, and environmental Sustainability. This study sought to identify several scientific studies that state how critical legal aspects are to environmental occupation and the management of citizens so that the environment can be sustainable. This study utilized secondary data from several books and scientific articles that actively discuss ecological and safety issues. After a series of reviews, we managed to find several important things, including how the definition of environmental Law; then we saw the scientific substance related to how the government should be given to citizens, then the legal aspects and existing systems, then also how the environmental aspects and the role of the government in implementing the Law and also the role of the government. The private sector in saving the environment. It is hoped that these findings will be helpful for future studies.